Evolução geomorfológica de fundo de vale agradacional da Volta Grande, alto curso do rio Uruguai, sul do Brasil - Santos, Matheus Vinícius dos (2023)
Fluvial valleys can be defined as forms depressed and excavated by watercourses over time, which evolve based on base-level or paleohydrological dynamics. They are composed by geomorphic units, which are formed both by the dynamics of the fluvial channel and the slopes to the interfluve. In the Volta Grande area, the fluvial valleys already studied have their stratigraphic records belonging to the Upper Pleistocene and Holocene, varying between alluvial and colluvial deposits. In order to understand the evolutionary process of the low-order basins in the Volta Grande area, this research aimed to map the geomorphological units within the Seção Quatro river watershed, analyze and interpret the evolutionary process of aggradation that occurred in this valley floor and establish its chronology. For these purposes, the mapping of geomorphological units was made by means of photointerpretation and the description of litho-, allo-, pedo- and chronostratigraphic criteria of pedostratigraphic sequences, and optically stimulated luminescence (LOE) datings were also realized. The mapping resulted in seven geomorphological units: plateaus, slope, agradational colluvium ramp, degradational colluvium ramp, alluvial fans, bedrock valleys, agradational valley and floodplain of the Uruguay River. About the stratigraphy, conglomeratic fluvial deposits supported clasts were identified, in addition to hydromorphic muddy gravel at the base of the stratigraphic sequence between the chronologies 19,000-15,000 years BP. Overlying the fluvial deposits are colluvial deposits, mostly of mud sand class, which were transported to the valley floor by sediment gravity flow (SG), identified between the chronologies 15,000- 9,000 years BP. The sediment gravity flow were interspersed with periods of minimal vegetation occupation, a fact identified by the predominance of the dark brown color in the stratigraphic sequence. There are still open questions regarding the cause of the sediment gravity flow identified in the study area, therefore, it is possible that these flows were triggered by mechanisms associated either with climatic oscillations or variations in the base level of the Uruguay River.